Ranking and assignment of priorities to watersheds of arid and semiarid zones of Chile. Part I: Method - Iroume A., Andres; Gayoso A., Jorge (Bosque (Valdivia), 1990)
A method based on the use of index as a technique to rank and assign priorities to watersheds of arid and semiarid zones of Chile is described. Three criteria and 12 parameters were chosen to represent watershed characteristics and to assign a numerical value to each watershed. The numerical value is used to rank the watersheds and to classify them into priority classes with the assistance of cluster analysis. The method is described in this paper. The testing and sensitivity analysis results will be described in a future paper.